Mapping tourism, sustainability, and development in Southeast Asia - Trupp, Alexander *; Dolezal, Claudia; Bui, Huong T. (Routledge, 2020)
Tourism in Southeast Asia traces back many years, with early forms of travel including pilgrimage, and travel for trade, land, resources, missions and warfare. Tourism is thus a long-established economic, religious, and social activity in the region though mass tourism is a rather recent phenomenon which largely began to expand in the 1970s. In the past decades, tourism in Southeast Asia has seen unprecedented growth while the region has also undergone major changes in relation to markets, mobility and integration between countries in economic and political terms. The creation and expansion of the Association of Southeast Asian Nations from a defence alliance to a political and economic relationship between member countries is significant in the formation of the Southeast Asian identity. The Philippines were isolated from airline connections for many years but experienced tourism growth as access options improved. The chapter also presents an overview of the key concepts discussed in this book.